2019
DOI: 10.1055/a-0885-9872
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Resistance Training Increases APPL1 Content in the Liver and the Insulin Sensitivity of Mice Fed a Long-term High-fat Diet

Abstract: Background APPL1, an adapter protein, interact directly with adiponectin receptors mediating adiponectin signaling and acting as a critical regulator of the crosstalk between adiponectin and insulin signaling pathway. The inadequate level of physical activity, high-calorie intake, or both lead to adverse consequences on health, like insulin resistance. On the order hand, physical exercise acts positively in the insulin action. Purpose Here, we investigated the effects of short-term resistance training (RT) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Also, Domingos et al, (2012) reported activation of the AMPK pathway and stimulation of lipid oxidation in the liver following resistance training, which decreased lipogenic enzymes such as SREPB-1c, ACC, SCD-1, and fatty acid synthase (19). Resistance training improves IR in rats fed a high-fat diet (28). It appears that in our study, adding sucrose solution along with a high-fat diet had a significant effect on IR, and PRT could not have a significant effect on IR and consequently the expression of these enzymes.…”
Section: Discussionmentioning
confidence: 98%
“…Also, Domingos et al, (2012) reported activation of the AMPK pathway and stimulation of lipid oxidation in the liver following resistance training, which decreased lipogenic enzymes such as SREPB-1c, ACC, SCD-1, and fatty acid synthase (19). Resistance training improves IR in rats fed a high-fat diet (28). It appears that in our study, adding sucrose solution along with a high-fat diet had a significant effect on IR, and PRT could not have a significant effect on IR and consequently the expression of these enzymes.…”
Section: Discussionmentioning
confidence: 98%
“…The results show that short-term RT increased the APPL1 content, which was accompanied by an improvement in insulin sensitivity. 37 To investigate the effects of IKKϵ deletion, Chiang and colleagues 38 observed an increased energy expenditure and protection from the negative impacts of a high-fat diet in knockout (KO) IKKϵ mice, suggesting a relation of IKKϵ in the thermogenesis pathway, such as uncoupling protein 1 (UCP1) expression. Additionally, in the liver, it was shown that IKKϵ content was elevated after high-fat feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Data report that hepatic Akt and IRS1 phosphorylation was higher in the exercised group than in the obese sedentary by reducing protein‐tyrosine phosphatase 1B (PTP1B) 36 . Minuzzi et al 37 also investigated the effects of short‐term resistance training (RT) on APPL1 content and adiponectin pathway in the liver of mice fed a long‐term high‐fat diet. The results show that short‐term RT increased the APPL1 content, which was accompanied by an improvement in insulin sensitivity 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RT was executed according to the protocol described by Minuzzi with several adjustments [22]. First, an empty weight-bearing device was immobilized on the tail while the mice were acclimated to the ladder.…”
Section: Maximum Voluntary Carrying Capacity (Mvcc) Test and Resistan...mentioning
confidence: 99%